2015
DOI: 10.4103/2141-9248.160185
|View full text |Cite
|
Sign up to set email alerts
|

Vulvovaginal candidiasis in Aminu Kano teaching hospital, North West Nigeria: Hospital-based epidemiological study

Abstract: Background:Vulvovaginal candidiasis (VVC) remains a common problem worldwide and the role of douching as a predisposing factor is unclear.Aim:This study was undertaken to highlight the prevalence and predisposing factors of VVC in North-west Nigeria.Subjects and Methods:This was a prospective study done at Aminu Kano Teaching Hospital (AKTH), North-west. AKTH is a 500-bed tertiary hospital located in Kano, the most populous state in Nigeria. Ethical clearance was obtained. Three hundred patients with VVC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
4
7
4
Order By: Relevance
“…The predominance of BV over the other two causes of vaginitis is consistent with the findings among reproductive-aged women from distantly separated countries worldwide, including Indonesia, southwestern Nigeria, Nepal, Iran, Turkey and Grenada [18, 25, 33, 3638]. In contrast, VVC was the most prevalent cause of vaginitis among sexually active adolescents from Brazil [21] and reproductive-aged women seeking medical care in Ethiopia and northeastern/northwestern Nigeria [35, 39, 40].…”
Section: Discussionsupporting
confidence: 81%
“…The predominance of BV over the other two causes of vaginitis is consistent with the findings among reproductive-aged women from distantly separated countries worldwide, including Indonesia, southwestern Nigeria, Nepal, Iran, Turkey and Grenada [18, 25, 33, 3638]. In contrast, VVC was the most prevalent cause of vaginitis among sexually active adolescents from Brazil [21] and reproductive-aged women seeking medical care in Ethiopia and northeastern/northwestern Nigeria [35, 39, 40].…”
Section: Discussionsupporting
confidence: 81%
“…We found that the frequency of VVC in our study is higher than the rates found in Nigerian (14.0%), Indian (20.47%), and Turkish (16%) studies (6,33,34). On the other hand, a very high prevalence of VVC (84.5%) was reported by Ugwa from North-West Nigeria (35). In contrast, the lowest frequency of infection was recorded in Brazil (5.44%) (36).…”
Section: Discussioncontrasting
confidence: 72%
“…The result of this study was in agreement with other studies that reported prevalence rate of 25%, 18.5% and 19% [17,18,19]. However, in contrast to the current study, higher VVC prevalence rates were reported in Nigeria by EA Ugwa (84.5%) [20] and in India by Kalia N et al (31%) [21]. On other hand, in a study conducted by Emeribe et al [22], among population that consisted of highly educated women with good personal hygiene, a low VVC prevalence rate of 14% have been reported.…”
Section: Discussionsupporting
confidence: 91%